PENERAPAN AKAD SALAM DAN ISTISHNA’ DALAM PERNIAGAAN KONTEMPORER DITINJAU DARI AYAT DAN HADIS AHKAM - Mufitasari, Dwi Nur; Ni'mah, Zulfatun; Adistalaili, Maya Asri (Ahkam: Jurnal Hukum Islam, 2024)
This paper aims to analyze the application of the salam and istishna’ contracts in contemporary business in terms of the ahkam verses and hadith. This research uses a literature method with a normative juridical approach, examining theories, concepts and regulations related to the salam and istishna’ contracts. The Data were collected from documents from sharia financial institutions and literature on greetings and istishna’, the Al-Qur'an, hadith and were analyzed using content analysis. The findings of the research show that the implementation of the salam and istishna’ contracts in sharia financial institutions as a contemporary business subject is in accordance with the provisions of the Qur'an Al-Baqarah verse 282. Moreovet, it has been carried out with a written agreement, recorded by an authorized official, namely a notary and carried out in the presence of two witnesses, in accordance with QS. An-Nisa verse 29. Another reason is that it does not contain elements of falsehood and is in accordance with the Hadith of the History of Ibnu Majah Number2185 and it applies the principle of like and like.